At the Turning Point of the Current Techno-Economic Paradigm: Commons-Based Peer Production, Desktop Manufacturing and the Role of Civil Society in the Perezian Framework - Vasilis Kostakis (tripleC: Communication, Capitalism & Critique)
Following the theory of techno-economic paradigm shifts (TEPS), this paper calls attention to the phenomenon of Commons-based peer production (CBPP). In the context of the current paradigm, it argues that civil society can play an important role in creating favourable conditions for a more sustainable global knowledge society. Approaching tentatively the ways in which 3D printing and other desktop manufacturing technologies can be used in CBPP, it also explores the ways in which the partnership with the state may provide a supportive innovative institutional basis for taking the maximum advantage of the emerging synergies in the vein of TEPS theory.